2020
DOI: 10.2147/ott.s242386
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of OSR1 Promotes Colon Adenocarcinoma Progression via FAK-Mediated Akt and MAPK Signaling</p>

Abstract: Introduction: Odd-skipped related transcription factor 1 (OSR1) is a newly identified tumor suppressor in many tumor types. However, the role and mechanism of OSR1 in colon adenocarcinoma (COAD) remain unknown. Methods: OSR1 expression was detected in COAD tissues and cells. COAD cells with OSR1 overexpression or knockdown were analyzed by in vitro CCK-8, transwell and flow cytometry assays, and by in vivo xenograft model. Results: OSR1 expression was downregulated in COAD and low expression level of OSR1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Odd-skipped related 1 (OSR1) is an odd-skipped family zincfinger protein (So and Danielian, 1999). OSR1 plays a vital role in heart and urogenital development, such as of kidneys and colon (Wang et al, 2005;Zhang and Jiang, 2020). In our study, it was found to play an important role in VV, suggesting that it can be a novel target for further studies.…”
Section: Discussionmentioning
confidence: 76%
“…Odd-skipped related 1 (OSR1) is an odd-skipped family zincfinger protein (So and Danielian, 1999). OSR1 plays a vital role in heart and urogenital development, such as of kidneys and colon (Wang et al, 2005;Zhang and Jiang, 2020). In our study, it was found to play an important role in VV, suggesting that it can be a novel target for further studies.…”
Section: Discussionmentioning
confidence: 76%
“…[20][21][22] For example, Zhang and Jiang showed that odd-skipped related transcription factor 1 (OSR1) affected HCC progression and induced apoptosis by inhibiting MAPK pathways. 23 They also mentioned that SN38 could induce the activation of the MAPK pathway and promote autophagy, thereby reducing the chemoresistance of tumor cells. 24 Hepatocellular carcinoma exhibited an elevated mutational burden compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Colon adenocarcinoma (COAD), as the most common type of colon cancer, ranks fourth most common cancer by incidence and the second leading cause of cancer-related deaths worldwide (18,19). Although the diagnosis and treatment of COAD patients are much improved, the survival rate of these patients remains unsatisfactory, mostly due to the latediagnosis (20,21). Increasing data has indicated the correlation of the immune cell infiltration in colon cancer with the patients' clinical outcomes (22).…”
Section: Introductionmentioning
confidence: 99%